HUBUNGAN MOTIVASI DALAM PENCEGAHAN KANKER SERVIKS DENGAN SIKAP UNTUK MELAKUKAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT PADA IBU USIA SUBUR DI WILAYAH KERJA PUSKESMAS RANDUAGUNG LUMAJANG - Mulyati, Tri Retno; Ermawati, Iit; Sary, Yessy Nur Endah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Cervical cancer has become the leading cause of death from cancer among women. The IVA test can detect early cervical cancer by differentiating normal and abnormal cervix to identify precancerous lesions. This study aims to analyze the correlation between motivation in cervical cancer prevention and attitude to carry out a visual inspection of acetic acid in women of childbearing age in the Working Area of the Randuagung Lumajang Health Center. The research design used correlation with a cross-sectional approach. The population in this study were women of childbearing age involving 158 respondents. The sampling technique used is simple random sampling. Data were collected using the client motivation for therapy scale (CMOTS) questionnaire and attitude and practice toward cervical cancer.The data were analyzed using Predictive Analytics SoftWare Version 18 with the Spearman Rho test at a significance level of α<0.05. The results showed that women of childbearing age had weak motivation in preventing cervical cancer (67.1%) and had less attitude to carry out a visual inspection of acetic acid (67.7%). It is also known that there is a correlation between motivation in preventing cervical cancer and attitude to carry out a visual inspection of acetic acid in women of childbearing age (p-value = 0.000 (r) 0.741). Having good motivation about cervical cancer prevention is significantly and positively related to the mother's attitude towards cervical cancer screening. Therefore the findings of this review provide important clues that it is necessary to address the process of regulation of motivation and simultaneously consider individuals and correlation in the use of health services, in this case, involvement in examinations.